Experimental study of direct contact condensation of spent vapor in a cocurrent flow packed tower under negative pressure - Xufeng Yu; Feng Guo; Dingkun Peng; Qunwu Huang (Energy Science & Engineering, 2023)
Abstract Condensers are often required in power generation systems to condense the exhaust steam generated at the end of the turbine. This paper will investigate the enhanced condensation process of spent steam in a parallel flow type. The operating parameters of steam temperature (Tcond), steam flow rate (Gin), cooling water temperature (Tin), and cooling water flow rate (Lw) will affect the condensation effect by changing the gas–liquid arrangement in the tower. In this experiment, an orthogonal test was designed in the Raschig ring to investigate the significance of these four operating parameters on the experimental results. Different types of packings have different condensation effects due to different accumulation methods. The same type of packing has a different surface area, resulting in different contact areas between the gas and liquid phases during condensation. In this experiment, four different packings will be investigated to find their condensation performance. This paper uses the size of subcooling (ΔT) as an indicator to evaluate the effectiveness of condensation, and the values of condensation rate (R), number of liquid phase heat transfer units (NTUL), and total volume heat transfer coefficient (Kv) are used as a reference for the effectiveness of condensation. The results show that the overall condensation effect of regular packing is better than that of random packing, The average condensation rate of regular packing is 95%, the average condensation rate of random packing is 90%, the subcooling of regular packing is about three to five smaller than that of random packing, the heat transfer coefficient of regular packing is about 1.5 times of that of random packing. And by fitting the Kv data for different packings, an empirical formula was obtained that can be used to predict the Kv size of other packings.